(3Jbhje GdfXQ aj eSGFd GdNdGas - (3GHf GdOgGf , aNQ GdOjf CHh TLGY eMeO Hf Ydj Hf TYjH Hf GdOgGf GdHZOGOj GdTGaYj,J (B592 (3g` s
(3ChdgG (B:s
(3cGf GdhGdO QVi Gddg Yfg jNJGQ di eG jNJGQ GdCH GdHQ dhdOg ef SYGOJi GdOfjG hGdCNQI s
(3BNQgG (B:s
(3jfJgi CKfGA GdMOjK Ydi CUd GdLOd s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B15s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B315s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdabg GdTGaYjs